A contribution to a theory of the dynamic mechanisms of Post-traumatic Stress Disorder in South African detainees - Solomons, Kevin (PINS-Psychology in Society, 2025)
The theoretical formulations in this paper are derived from clinical experience in the Detainees Counselling Service in Johannesburg. This service is provided voluntarily by trained psychotherapists for people who have been detained on political grounds. The service emerged as a result of the growing realization that a significant proportion of ex-detainees suffered from debilitating and serious psychological sequelae which could be attributed directly to their detention experience. (Rasmussen, 1982; Lunde, 1982). This experience often included both physical and psychological forms of torture (Katz. 1982; Foster & Sandler, 1985). Over the past three years, the service has offered counselling to over 500 affected people. Increasing numbers of people are presenting as a result of traumas sustained outside the prisons and in their communities at the hands of security forces, rival political groupings, or both. This is part of the pattern of escalating political and social violence that has gripped the country. The paper will examine the following: the necessary preconditions for the development of PTSD; the impact on the ego of serious trauma; the ego transformations induced by the trauma.